Evaluation of Quality of Life in the Elderly With Chemotherapy-induced Peripheral Neuropathy in Selected Educational Centers of Iran University of Medical Sciences in 2020 - Mohamad Masoud Hasani; Farideh Bastani (Iran University of Medical Sciences, 2022)
Background & Aims: Peripheral neuropathy due to chemotherapy is one of the serious complications of chemotherapy and its negative effects on various aspects of patients' lives can not be denied. The aim of this study was to determine the quality of life of the elderly with peripheral neuropathy due to chemotherapy in selected educational and medical centers of Iran University of Medical Sciences in 2016. Materials & Methods: The present study was a cross-sectional (descriptive) study. The study population was the elderly with chemotherapy-induced peripheral neuropathy referred to the educational and medical center of Iran University of Medical Sciences. 170 people were selected by continuous sampling method. Data collection tools included demographic characteristics form and Lipad quality of life questionnaire (LEIPAD) and research data were completed during 3 months (from September 1399 to November 1399). Data were analyzed using descriptive and inferential statistics using SPSS software version 16 at a significant level (P<0.05). Results: The average quality of life of the elderly based on the total score was 59.37 14 14.29 (high quality of life) and based on zero to one hundred was equal to 63.84 15 15.37. The highest score was related to the mental function dimension with a score of 86.06 19 18.19 and the lowest score was related to sexual function with a score of 9.5 18 18.11. The results showed that the quality of life of most elderly people was at a high level (81.8%). Quality of life of the elderly with gender (P=0.003), comorbidities (P=0.045), income adequacy (P=0.002), employment status (P<0.001) and duration of illness (P=0.019) had a statistically significant relationship. The results of linear regression showed that the variables of employment status (unemployed) (P=0.041), duration of illness (P=0.033) and comorbidities (P=0.030) significantly affected the quality of life of the elderly Has had an impact. Findings showed that 0.22% of changes in quality of life can be explained by independent variables. Conclusion: Considering that the research samples were more than the young elderly group, ie between 60 and 74 years old, and were not very old and disabled, and a significant percentage of them were married and benefited from family support, far from It was not expected that their quality of life would not be overshadowed and assessed as desirable, despite facing a cancer crisis, chemotherapy intervention, and neuropathic symptoms. However, the quality of life in the sexual dimension was poorer, which requires counseling interventions and more attention from health planners.